L-Arginine-Nitric Oxide-Asymmetric Dimethylarginine Pathway and the Coronary Circulation: Translation of Basic Science Results to Clinical Practice - Cziráki, Attila; Lenkey, Zsófia; Sulyok, Endre; Szokodi, István; Koller, Akos (Frontiers in Pharmacology, 2020)
By 1980, it was thought that we already knew most of the major mechanisms regulating vascular tone. However, after the somewhat serendipity discovery that endothelium is involved in mediation of relaxation to acetylcholine, a whole new world opened up and we had to rewrite our concept regarding vascular function and its regulation (not to mention many other fields). The new player was an endothelium derived relaxing factor, which molecular constitution has been identified to be nitric oxide (NO). This review summarizes the major molecular steps concerning how NO is synthetized from L-arginine. Also, the fate of L-arginine is described via the arginase and methylation pathways; both of them are affecting substantially the level and efficacy of NO. In vitro and in vivo effects of L-arginine are summarized and controversial clinical findings are discussed. On the basis of the use of methylated L-arginines, the vasomotor effects of endothelial NO released to agonists and increases in flow/wall shear stress (a major biological stimulus) is summarized. In this review the role of NO in the regulation of coronary vascular resistance, hence blood flow, is delineated and the somewhat questionable clinical use of NO donors is discussed. We made an attempt to summarize the biosynthesis, role, and molecular mechanisms of endogenously produced methylated L-arginine, asymmetric dimethylarginine (ADMA) in modulating vascular resistance, affecting the function of the heart. Additionally, the relationship between ADMA level and various cardiovascular diseases is described, such as atherosclerosis, coronary artery disease (CAD), ischemia/reperfusion injuries, and different types of coronary revascularization. A novel aspect of coronary vasomotor regulation is identified in which the pericardial fluid ADMA and endothelin play putative roles. Finally, some of the open possibilities for future research on L-arginine-NO-ADMA signaling are highlighted.